Microencapsulation by spray coagulation method: Study of the alginate crosslinking by different calcium salts - Cuma, Diana Francisco (2019)
The use of biopolymers such as alginate has been growing in the last decades due to properties such as non-toxicity and biodegradability. In this work, the microencapsulation of curcumin and safranin, used as model compounds for hydrophobic and hydrophilic active principles, respectively, was studied with alginate matrices by the spray coagulation technique. The alginate ionic crosslinking with three calcium sources (calcium chloride (CaCl2), calcium gluconate and calcium lactate) was considered. The obtained microcapsules were characterized in terms of load, encapsulation efficiency (EE), rehydration capacity, and particle size. The release profiles of both active principles were also studied. Through FTIR analysis the contribution of the calcium source, and the presence of the active principles inside the microcapsules, was identified, while the TGA evidenced an increasing of the thermal stability due to the alginate crosslinking effect, particularly when CaCl2 was used. The overall results showed that CaCl2 is the most effective calcium source for alginate crosslinking, while calcium lactate lead to a more gradual release of the active principles.